Modification of Activated Carbon KAU Surface Properties - Brazhnyk, D.V.; Bacherikova, I.V.; Zazhigalov, V.A.; Kowal, A. (Хімія, фізика та технологія поверхні, 2011)
The properties of oxidized activated carbon KAU treated at different temperatures in inert atmosphere were studied by means of DTA, Boehm titration, XPS and AFM methods and their catalytic activity in H2S oxidation was established. Three types of oxygen species exist on carbon catalysts surface. It was shown that their catalytic activity in hydrogen sulfide oxidation correlated with relative content of OH-groups and charged oxygen species on carbons surface (O2.1 and O3.1 oxygen types with BE = 533.2–533.7 and 536.8–537.6 eV, respectively). The sample treated at 1000°C has very high activity in H2S oxidation and transforms up to 57 mmol H2S/g cat at 180°C. The vanadium/carbon KAU samples were prepared by three different methods (incipient wet impregnation and deposition-precipitation by NH4VO3 in aqueous medium, and in acetonitrile with VO(acac)2). It was established that synthesis in organic medium led to preparation of nanodispersed vanadia on carbon surface. The V/C samples were more active in H2S oxidation at 180° C than treated activated carbons. The sample prepared in organic medium had excellent activity in hydrogen sulfide oxidation and oxidized more than 132 mmol H2S/g cat without its deactivation. The formation of surface dense sulfur layer is the reason of catalysts deactivation in H2S selective catalytic oxidation.